Clinical relevance of brain atrophy assessment in multiple sclerosis. Implications for its use in a clinical routine. (2nd July 2016) - Zivadinov, Robert; Jakimovski, Dejan; Gandhi, Sirin; Ahmed, Rahil; Dwyer, Michael G.; Horakova, Dana; Weinstock-Guttman, Bianca; Benedict, Ralph R. H.; Vaneckova, Manuela; Barnett, Michael; Bergsland, Niels
ABSTRACT: Introduction: Brain atrophy measurement in multiple sclerosis (MS) has become an important outcome for determining patients at risk for developing physical and cognitive disability. Areas covered: In this article, we discuss the methodological issues related to using this MRI metric routinely, in a clinical setting. Understanding trajectories of annualized whole brain, gray and white matter, thalamic volume loss, and enlargement of ventricular space in specific MS phenotypes is becoming increasingly important. Evidence is mounting that disease-modifying treatments exert a positive effect on slowing brain atrophy progression in MS. Expert Commentary: While there is a need to translate measurement of brain atrophy to clinical routine at the individual patient level, there are still a number of challenges to be met before this can actually happen, including how to account for biological confounding factors and pseudoatrophy, standardize acquisition and analyses parameters, which can influence the accuracy of the assessments.